2021
DOI: 10.1073/pnas.2107507118
|View full text |Cite
|
Sign up to set email alerts
|

Multispecific targeting of glioblastoma with tumor microenvironment-responsive multifunctional engineered NK cells

Abstract: Tumor antigen heterogeneity, a severely immunosuppressive tumor microenvironment (TME) and lymphopenia resulting in inadequate immune intratumoral trafficking, have rendered glioblastoma (GBM) highly resistant to therapy. To address these obstacles, here we describe a unique, sophisticated combinatorial platform for GBM: a cooperative multifunctional immunotherapy based on genetically engineered human natural killer (NK) cells bearing multiple antitumor functions including local tumor responsiveness that addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 57 publications
0
56
0
Order By: Relevance
“…The microenvironment (TME) plays an essential role in the progression and metastasis of GBM. 33 Generally, TME is enriched for pro-inflammatory cytokines, chemokines, and their complex cross-talk with their receptors influences the development of cancers. 23 For example, macrophages can be recruited into the tumor microenvironment by the CCL2-CCR2 signaling, associated with poor patient prognosis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The microenvironment (TME) plays an essential role in the progression and metastasis of GBM. 33 Generally, TME is enriched for pro-inflammatory cytokines, chemokines, and their complex cross-talk with their receptors influences the development of cancers. 23 For example, macrophages can be recruited into the tumor microenvironment by the CCL2-CCR2 signaling, associated with poor patient prognosis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 223 In glioblastoma, pharmacological inhibition of autophagy by chloroquine promoted the expression of the chemokines CCL5 and CXCL10 by tumor cells, enhancing infiltration of CAR NK cells into the tumor tissues. 224 We reported that herpes simplex virus 1-based oncolytic virus increased NK cell infiltration in various mouse models of glioblastoma. 225 231 However, the detailed mechanisms underlying the interaction between chemokines and their receptors have yet to be explored.…”
Section: Trafficking Of Nk Cells Into Tumorsmentioning
confidence: 96%
“…Furthermore, in a gastric cancer study, the intratumorally NK cells (CD57 + ) were associated with poor outcomes [ 266 ]. Another study showed that the pharmacologic impairment of autophagy functions acts as an immuno-modulator and promotes the genetically-engineered human NK cells into tumor sites, resulting in effective anti-GBM activity [ 267 ]. Therefore, more studies are required in order to determine the intra-tumoral impact of infiltrated NK cells and their therapeutic efficacy.…”
Section: Other Immune Cells In Tumor Microenvironment and New Techniq...mentioning
confidence: 99%